Integrasi Literasi Digital dan Nilai-Nilai Pendidikan Islam dalam Meningkatkan Critical Thinking Mahasiswa di Era Artificial Intelligence - M. Thoriq Aziz; Syamsul Ma’arif (Al-Absah: Journal of Civilization, Language, Literature, and History, 2026)
Abstract: This study aims to analyze the integration strategies of digital literacy and Islamic educational values, alongside their implications for enhancing students' critical thinking skills amidst the massive utilization of Artificial Intelligence (AI). The research employed a descriptive qualitative method with a case study approach in an Islamic higher education institution. Data collection was carried out through in-depth interviews, participatory observation, and documentation of students' academic activities. The results indicated that the instant utilization of AI technologies risks degrading students' analytical sharpness. However, a curriculum reconstruction that blends digital literacy skills such as information validation and comparative thinking with Islamic epistemological values (the principles of tabayyun and tafakkur) proved effective as both an ethical filter and a stimulant for critical reasoning. The study concludes that the integration of technological and Islamic axiological aspects successfully transforms students' roles from mere consumers of AI platforms into critical and adaptive information evaluators. This integration model is recommended as a tactical blueprint for policymakers in Islamic higher education to effectively respond to digital technology disruptions. Keywords: Artificial Intelligence; Critical Thinking; Digital Literacy; Islamic Education; Undergraduate Students.